Dominasi Keterpaksaan dalam Budaya Kawin Tangkap pada Novel Perempuan yang Menangis Kepada Bulan Hitam Karya Dian Purnomo: Kajian Marxisme - Irawan, Mohammad (Jurnal Pena Indonesia, 2024)
This research explains the domination of compulsion in the culture of captive marriage contained in the novel entitled “Perempuan yang Menangis Kepada Bulan Hitam” by Dian Purnomo as a form of representation related to the culture of the Sumbanese people through the lens of Karl Marx's hegemony. The aim of this research is to determine the form of domination of the structural role of the strong upper class over the subaltern class in the form of violence and coercion. This research refers to the use of descriptive qualitative methods using Karl Marx's theory of hegemony with intensive listening techniques. The results of the research show that there is the influence of Karl Marx's hegemony and the cultural practice of captive marriage in the novel “Perempuan yang Menangis Kepada Bulan Hitam”. Keywords: captive marriage, culture, hegemony, marxism.